Essential oil from the aerial part of Orchidantha vietnamica K. Larsen and its antimicrobial activity - Son, Ninh The; Danh, Nguyen Duc; Anh, Le Tuan; Thuy, Dinh Thi Thu; Luyen, Nguyen Dinh; Tuyen, Tran Thi (Vietnam Journal of Science and Technology, 2022)
The hydro-distilled essential oil from the fresh aerial part of Orchidantha vietnamica K. Larsen collected from Lamdong-Vietnam was analyzed by GC-FID (Gas Chromatography-Flame Ionization Detection) and GC-MS (Gas Chromatography-Mass Spectroscopy) for the first time. The oil was characterized by the presence of volatile compounds type terpenoids, in which oxygenated monoterpenes (30.04 %) and sesquiterpene hydrocarbons (37.32 %) are the major components. The oxygenated monoterpene linalool reached the highest percentage of 16.66 %, followed by the sesquiterpene hydrocarbons (E)-caryophyllene (11.4 %), α-humulene (8.00 %), and bicyclogermacrene (6.93 %). Monoterpene hydrocarbons, oxygenated sesquiterpenoids, oxygenated diterpenes, carotenoids, and others are also detected in this oil (< 3.00 %). The essential oil of O. vietnamica aerial part showed antimicrobial activity against two pathogenic bacterial strains Escherichia coli ATCC 8739 and Candida albicans ATCC 10231 with the same MIC (Minimum Inhibitory Concentration) value of 200 µg/mL.